Pengaruh Kode Etik Guru Terhadap Proses Pembelajaran - Feronica Simanjuntak; Dorlan Naibaho (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The aim of this research is to analyze the influence of the teacher's code of ethics on the student learning process. The research used quantitative research methods with a sample of 100 secondary school teachers and 200 students. The research results show that a teacher's code of ethics has a significant impact on the learning process, especially on improving the quality of teaching, developing students' self-confidence, and creating a positive learning environment. A teacher's code of ethics also influences students' learning motivation and academic achievement. Therefore, there is a need to increase awareness and practice of teachers' codes of ethics in the learning process. The Teacher Code of Ethics provides guidelines for teachers in carrying out their duties as educators, community members and citizens. This Code of Ethics is designed to ensure that teachers act and behave in accordance with high moral and professional standards. The influence of a teacher's code of ethics on the learning process can be studied from various aspects, such as: B. Teacher behavior in the classroom, teacher-student relationships, and teacher professional development efforts. The Teacher Code of Ethics emphasizes the importance of developing positive professional relationships with students. Teachers who adhere to a code of ethics tend to care more about students' welfare, respect differences, and create an inclusive learning environment. Additionally, students' personal data will be treated as confidential and data breaches will be prevented.